2023
DOI: 10.1002/advs.202300673
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Mimic, Fast‐Moving, and Flippable Soft Piezoelectric Robots

Abstract: Cheetahs achieve high‐speed movement and unique athletic gaits through the contraction and expansion of their limbs during the gallop. However, few soft robots can mimic their gaits and achieve the same speed of movement. Inspired by the motion gait of cheetahs, here the resonance of double spiral structure for amplified motion performance and environmental adaptability in a soft‐bodied hopping micro‐robot is exploited. The 0.058 g, 10 mm long tethered soft robot is capable of achieving a maximum motion speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Within the realm of small-scale planar crawlers, the key performance metrics include mass, speed, and power source, as depicted in Figure 5I. [1][2][3][4][5][6][7][8][10][11][12][13]17,19, Soft-crawling robots are predominantly externally powered and can weigh as little as 0.9 g. [19] Conversely, many rigid crawling robots utilize battery power and can weigh as little as 1.7 g. [2] The GASR possesses a light weight of 1.2 g and an average speed of 1.1 BL s −1 , nearly rivaling externally powered robots. Furthermore, robots employing unstable galumphing and vibration-based slipping are located within the red and blue regions of the performance space, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the realm of small-scale planar crawlers, the key performance metrics include mass, speed, and power source, as depicted in Figure 5I. [1][2][3][4][5][6][7][8][10][11][12][13]17,19, Soft-crawling robots are predominantly externally powered and can weigh as little as 0.9 g. [19] Conversely, many rigid crawling robots utilize battery power and can weigh as little as 1.7 g. [2] The GASR possesses a light weight of 1.2 g and an average speed of 1.1 BL s −1 , nearly rivaling externally powered robots. Furthermore, robots employing unstable galumphing and vibration-based slipping are located within the red and blue regions of the performance space, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When the output force F of the motor is sufficiently large to elevate the robot in air, it can galumph. Unlike previous soft robots that galumph unstably, [12,13] GASR can perform regular and predictable galumphing. As depicted in Figure 6D, four phases of motion are involved in a complete galumphing cycle: both-touching, A-touching, B-touching, and aerial.…”
Section: Modeling Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…( e ) Schematic of electrochromic principle and the disguise process by applied DC voltage; Reprinted with permission from the study presented in [ 49 ], License Number: 5760770707891, Copyright 2022 Wiley-VCH GmbH. ( f ) BFFSPR climbs a 12° slope and moves after falling and flipping from a high platform [ 50 ].…”
Section: Actuating Methodsmentioning
confidence: 99%
“…Vibration is a fast motion often observed in nature (like honeybees) and our daily lives (e.g., strings). Therefore, soft robots worked by vibration have attracted the attention of researchers due to their outstanding response time and output forces [ 50 ]. For example, Chen et al [ 50 ] reported a bionic piezoelectrical soft robot made of inverse piezoelectric-actuated PVDF film, Ag electrodes, and a passive layer film(Cu).…”
Section: Actuating Methodsmentioning
confidence: 99%